Exploring music-based attachment to video games through affect expressions in written memories - Tuuri, Kai; Koskela, Oskari; Tissari, Heli; Vahlo, Jukka (Elsevier, 2025)
This paper presents an exploratory research on music-based attachment to video games, studied through personally valued game music memories. It focuses on people’s engagement with game music and game technologies, expanding previous research on the role of game music in people’s lives. We gathered 183 written game music memories and analyzed their contents and language. We focused on expressions of affect and sentiment, which we assumed would indicate affective involvement. However, we also explored the constitution of attachment by investigating how expressions of affect and sentiment were associated with other aspects in the stories that reflect personal valuation, focusing specifically on factors of autobiographical remembrance, conceptualizations of game music, and gaming technology related to memories. These investigations employed a mixed-methods approach that combined qualitative and statistical analyses. A major finding was that especially personal remembrances that involved an awareness of the self or related to the game music experience significantly predicted the use of expressions of affect and sentiment in the stories. In sum, the study outlines a framework for investigating people’s long-term engagement with technology as being intimately related to the context of everyday life and the constitution of self-understanding.